Evaluasi Program Supervisi Akademik di PAUD Swasta - Kurniawan, Daniel; Dwikurnaningsih, Yari; Sulasmono, Bambang Suteng (Universitas Kristen Satya Wacana, 2018)
This study was designed to evaluate academic supervision program at PAUD Tunas Kasih, Magelang, using Context, Input, Process, Product (CIPP) evaluation model. The results of the study were expected to provide inputs to decision-makers for subsequent programs. The respondents of this descriptive-qualitative research included the school principal, six teachers, and a school managerial staff. Data collection was done through interviews, observation and document studies. Triangulation of data sources and methods validated the data, subsequently analysed through data condensation, data display, conclusion drawing and verification. Findings indicated the context evaluation revealed a need for academic supervision based on the condition and the need for teacher’s quality improvement. The input evaluation described the well-planned program—using different techniques, involving the teachers in their readiness, supported by available budget and infrastructure. The process evaluation reported the implementation of the planned techniques, with some adjustments based on the on-going condition, supported by the teachers’ readiness as well as participation and how they handle the constraints. The product evaluation found out that the academic supervision program had positive impacts and achieved the planned goals. It also discovered teachers’ positive responses and some follow-up plans. Lastly, this study gave recommendations to improve the local supervision programs, inputs to the school management, and ideas for future researches.